Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Ac Daikin Pt. Mitra Indo Teknik - Evitha, Yuli; Amalliah, Dwi Putri (JAMBIS : Jurnal Administrasi Bisnis, 2025)
In the air conditioning industry, business face intense competition in terms of both pricing and product quality. The sales instability observed at Pt. Mitra Indo Teknik indicates underlying issues influencing purchasing decisions. This research aims to analyze the extent to which product quality and price influence the purchasing decisions of Daikin air conditioners at Pt. Mitra Indo Teknik. This research adopts a quantitative approach. The population consist of all customer of Pt. Mitra indo Teknik who have purchased Daikin air conditioners. The result reveal a positive and significant influence of product quality on purchasing decisions, with a calculated tvalue of 10.897 ttable value of 1.980 and a significance value of 0.000 < 0.05 likewise, price has a positive and significant influence on purchasing decisions, with a calculated t-value of 2.831 > t-table value of 1.980 and a significance value of 0.005 < 0.05. Simultaneously, product quality and price have a positive and significant influence on purchasing decisions, as indicated by an F-test value of 73.109 > F-table value of 3.07 and a significance level of 0.000 < 0.05. The Combined contribution of product quality and price to purchasing decisions is 53.9%, while the remaining 46.1% is influenced by other variables not examined in this research.